Verapamil and Alzheimer’s Disease: Past, Present, and Future - Popović, Natalija; Morales-Delgado, Nicanor; Vidal Mena, David; Alonso, Antonia; Pascual Martínez, María; Caballero Bleda, María; Popović, Miroljub (Frontiers in Pharmacology, 2020)
Verapamil is a phenylalkylamine class calcium channel blocker that for half a century has been used for the treatment of cardiovascular diseases. Nowadays, verapamil is also considered as a drug option for the treatment of several neurological and psychiatric disorders, such as cluster headache, bipolar disorders, epilepsy, and neurodegenerative diseases. Here, we review insights into the potential preventive and therapeutic role of verapamil on Alzheimer’s disease (AD) based on limited experimental and clinical data. Pharmacological studies have shown that verapamil has a wide therapeutic spectrum, including antihypertensive, anti-inflammatory, and antioxidative effects, regulation of the blood-brain barrier function, due to its effect on P-glycoprotein, as well as adjustment of cellular calcium homeostasis, which may result in the delay of AD onset or ameliorate the symptoms of patients. However, the majority of the AD individuals are on polypharmacotherapy, and the interactions between verapamil and other drugs need to be considered. Therefore, for an appropriate and successful AD treatment, a personalized approach is more than necessary. A well-known narrow pharmacological window of verapamil efficacy may hinder this approach. It is therefore important to note that the verapamil efficacy may be conditioned by different factors. The onset, grade, and brain distribution of AD pathological hallmarks, the time-sequential appearances of AD-related cognitive and behavioral dysfunction, the chronobiologic and gender impact on calcium homeostasis and AD pathogenesis may somehow be influencing that success. In the future, such insights will be crucial for testing the validity of verapamil treatment on animal models of AD and clinical approaches.